Phytosociological description of mesophilous colline-submontane Fagus sylvatica and Carpinus betulus forests in Slovenian Istria - Dakskobler, Igor (Acta silvae et ligni, 2018)
A phytosociological analysis of 46 relevés of mesophilous colline and submontane Fagus sylvatica as well as (or) Carpinus betulus forests was conducted in Slovenian Istria. It was established that they are frequently syndynamically interrelated: in places, common hornbeam stands are merely a degradation stage on beech sites, and can be classified into the subassociation Ornithogalo pyrenaici-Fagetum fraxinetosum orni (its locus classicus is in the Goriška Brda Hills) and into the new subassociation Ornithogalo pyrenaici-Carpinetum betuli seslerietosum autumnalis. Compared with similar submontane stands from other parts of the western and southwestern Slovenia they are slightly poorer in species, with fewer diagnostic species of alliances Erythronio-Carpinion, Aremonio-Fagion and Tilio-Acerion, order Fagetalia sylvaticae and class Vaccinio-Piceetea, and with more diagnostic species of the order Quercetalia pubescenti-petraeae. Geographically, they are characterised by the taxon Helleborus odorus subsp. istriacus. Although they cover small areas these forests generate high yields and are therefore important both economically and as biotopes of protected species.
Keywords: phytosociology; Ornithogalo-Carpinetum; Ornithogalo-Fagetum; synsystematics; beech sites; fitocenologija; sinsistematika; bukova rastišča; Istra; Istria; Slovenia; Slovenija